Про деякі македонські й балканські прислів’я та приказки - Величковський, Б. (Народна творчість та етнографія, 2009)
The aim of this paper is the investigation of the common Balkan paroemiological layer which, in the Macedonian examples, is related to the folk expression containing numerous proverbial items that contain identical, equivalent or adequate parallels in the languages with which the Macedonian has been in direct contact in the Balkan linguistic milieu. In relation to these common proverbs and sayings it has to be stressed that it is not always an easy task to identify the language from which they originate, therefore the researcher very often finds himself in front of a big dilemma how to resolve it. However, sometimes the presence of some lexical and structural features in these paroemiological forms gives a clue by means of which it is possible to spot their source of origin. Thus, starting from this criterion, it can be concluded that a considerable stock of the Macedonian proverbs and sayings are of Oriental and Turkish origin. In general, these so-called short forms represent an essential part of the Macedonian folklore, which content is fairy rich and various, and they express the attitude of the people for they are the reflection of life with all the complexity throughout their history in this part of the Balkan Peninsula.